MOTIVASI, KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI BADAN PERENCANAAN PEMBANGUNAN DAERAH KABUPATEN TULUNGAGUNG DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVERNING - Banattha Noorrena; Imam Baehaqi (Universitas Islam Kadiri, 2021)
An organization is a group of cooperation between people which is held to achieve common goals. The organization is a form of association or an alliance made by two or more people to collaborate with each other in a formal bond. This study aims: (1) Analyze the influence of motivation on employee job satisfaction, (2) To analyze the effect of compensation on employee job satisfaction, (3) To analyze the effect of work environment on employee job satisfaction, (4) to analyze the influence of motivation on performance, (5) Analyze the effect of compensation on performance. (6) Analyzing the influence of the work environment on performance, (7) Analyzing the effect of job satisfaction on employee performance. (8) Analyzing the influence of motivation through job satisfaction on employee performance, (9) Analyzing the effect of compensation through job satisfaction on employee performance, (10) Analyzing the influence of the work environment through job satisfaction on employee performance. The results showed that: (1) motivation affects job satisfaction, (2) compensation affects employee job satisfaction, (3) work environment affects employee job satisfaction, (4) motivation affects employee performance, (5) compensation affects employee job satisfaction. Performance of the employees of the Regional Development Planning Agency of Tulungagung Regency. (6) The work environment affects employee performance, (7) Job satisfaction affects employee performance, (8) Job satisfaction is an interverning variable related to the influence of motivation on employee performance, (9) Job satisfaction is an interrelated variable related to the effect of compensation on employee performance. , (10) Job satisfaction is an interrelated variable related to the influence of the work environment on employee performance.